Age-related distribution and potential role of SNCB in topographically different retinal areas of the common marmoset Callithrix jacchus, including the macula. (August 2019) - Hadrian, Karina; Melkonyan, Harutyun; Schlatt, Stefan; Wistuba, Joachim; Wasmuth, Susanne; Heiligenhaus, Arnd; Thanos, Solon; Böhm, Michael R.R.
Abstract: Evidence of an age-related increase of β-synuclein (SNCB) in several parts of the visual system including the retina has been reported. SNCB is thought to function as an antagonist of α-synuclein in neurodegenerative diseases, but the exact role of SNCB remains unclear. The presented work studies two different aspects of the onset and role of SNCB in the retinal pigment epithelium (RPE). First, the topographical and intracellular distributions of SNCB in the RPE of non-human marmoset monkey ( Callithrix jacchus ) were evaluated in paraffin-embedded eyes and RPE whole mounts from different developmental stages (neonatal, adolescent, and adult). Thus, revealed distinct lifetime-related alterations of the topographical and intracellular distributions of SNCB in the primate macula compared to the retinal periphery. Furthermore, the function and influences of SNCB on ARPE-19 cells and primary porcine RPE (ppRPE) cells were characterized by exposing these cells with recombinant SNCB (rSNCB) at different concentrations. Moreover, apoptosis, protein- and mRNA-expression levels of factors of the p 53/MDM2 signaling cascade and inflammation- and oxidation-related genes were investigated. The observed dose-depended decreased apoptosis rates together with the PLD2 mediated activation of the p 53 pathway promotes senescence-related processes in SNCB exposed common ARPE-19 cells from human origin. Further, increased HMOX1 and NOX4 levels indicate increased oxidative stress and inflammatory responses triggered by SNCB. The obtained differences in the distribution of SNCB in primate RPE together with alterations of cellular functions in rSNCB-exposed RPE cells (e.g., ARPE-19, ppRPE) support SNCB-related effects like inflammatory response and stress-related properties on RPE over lifetime. The possible functional relevance of SNCB in physiological aging converting into a pathophysiological condition should be investigated in further studies. Highlights: The distribution and shape of pigmented granules change within the RPE over lifetime. SNCA and SNCB showed different age- and topography-related distributions in the RPE. SNCB-related activation of p 53 indicate its role in senescence-related conditions. SNCB-related Increase of NOX4 and HMOX1 imply oxidative stress and inflammatory responses. Comparable oxidative stress and inflammatory responses were found in porcine RPE.